Medium- vs. short-term consumer inflation expectations: Evidence from a new euro area survey - Ewa Stanisławska; Maritta Paloviita (Bank of Finland, 2021)
Using the ECB Consumer Expectations Survey, this paper investigates how consumers revise medium-term inflation expectations. We provide robust evidence of their adjustment to the current economic developments. In particular, consumers adjust medium-term inflation views in response to changes in short-term inflation expectations and, to a lesser degree, to changes in perceptions of current inflation. We find that the strong adverse Covid-19 pandemic shock contributed to an increase in consumer inflation expectations. We show that consumers who declare high trust in the ECB adjust their medium-term inflation expectations to a lesser degree than consumers with low trust. Our results increase understanding of expectations formation, which is an important issue for medium-term oriented monetary policy.
URN:NBN:fi:bof-202106291311
Keywords: D12; D84; E31; E58; 330; Inflation expectations; consumer survey; micro-data